2022
DOI: 10.3390/ijerph191912603
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Laser to Intravitreal Injections for Diabetic Retinopathy: Hospital Utilization and Costs from an Extended Healthcare Perspective

Abstract: Purpose: To describe the trends in hospital utilization and economic outcomes associated with the transition from laser to intravitreal injection (IVI) therapy for diabetic retinopathy (DR) at Oslo University Hospital (OUH), which provides the largest retina service in Norway. Methods: This descriptive study analyzed hospital administrative data and determined the average utilization and treatment proportions of laser therapy, IVIs and vitrectomy for each patient per year. The Chi-square test was used to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“… 12 This concept is widely accepted and might have altered the preferred practice pattern among Japanese doctors. Consequently, the increase in anti-VEGF injections may have contributed to a decline in the number of vitrectomies performed for proliferative retinopathy and retinal photocoagulation despite an increase in the number of diabetic patients 13 ( Table 5 , Figures 2a, b , and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“… 12 This concept is widely accepted and might have altered the preferred practice pattern among Japanese doctors. Consequently, the increase in anti-VEGF injections may have contributed to a decline in the number of vitrectomies performed for proliferative retinopathy and retinal photocoagulation despite an increase in the number of diabetic patients 13 ( Table 5 , Figures 2a, b , and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of intravitreal anti-VEGF drugs such as ranubizumab and aflibercept heralded an age of unprecedented benefit for those with center-involving diabetic macular edema, but due to short treatment intervals and the need for close monitoring, this created extreme demand on resources [ 42 , 43 ]. A systematic review of anti-VEGF treatment for diabetic macular edema found a significant treatment effect, yielding an improvement in vision of three or more lines of visual acuity to 30–40% of people at one year [ 44 ].…”
Section: Diabetic Retinopathymentioning
confidence: 99%